Camouflage orthodontic treatment combined with genioplasty distraction osteogenesis for skeletal class II relationship secondary to osteosarcoma excision surgery. Issue 7 (19th April 2022) - Liu, Zhixu; Wang, Xudong; Zhu, Min; Jiang, Lingyong; He, Yue; Tang, Guohua; Yang, Xiao
Abstract: Objective: The treatment of orthodontic patients who survive head and neck tumors is challenging because of dentoskeletal deformities and other unexpected dental and facial complications. This case report describes the case of a 26‐year‐old woman who presented with mandibular retrognathia after survival from osteosarcoma. Clinical considerations: Camouflage orthodontic treatment was chosen instead of combined orthodontic‐orthognathic surgery after primary reconstructive surgery with an iliac bone graft. Genioplasty distraction osteogenesis (DO) was performed to achieve an optimal facial profile. Although unexpected condyle dislocation and epithelial hyperplasia occurred during treatment, a favorable facial profile and optimal skeletal and dental relationships were accomplished after 32 months of treatment. Conclusions: The patient underwent genioplasty DO and experienced unexpected left condyle dislocation. However, the treatment achieved esthetic goals after intermaxillary elastics were applied.